Cover Picture: Macromol. Mater. Eng. 3/2015. Issue 3 (March 2015) - Singer, Julia C.; Ringk, Andreas; Giesa, Reiner; Schmidt, Hans‐Werner
<x xml:space="preserve">Abstract</x> Front Cover: Electrospinning is an attractive technique to generate supramolecular macro‐ and nanofibers. Here, a comprehensive structure‐property relationship between chemical structure, spinnability, and fiber morphology is presented for several classes of small molecules. For the characterization of electrospun morphologies, scanning electron microscopy (SEM) is the tool of choice. Among thousands of images taken in the course of a project, some pictures reveal very peculiar and curious details, with Pinocchio shown as the center piece. To discover such images during hours of tedious SEM work demonstrates that science can be a lot of fun. Further details can be found in the article by J. C. Singer, A. Ringk, R. Giesa, and H.‐W. Schmidt* on page 259. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>